The competition effect of new entry on mutual fund incumbents in China. Issue 1 (20th February 2017) - Feng, Xunan; Xu, Jin; Wang, Ying; Tang, Chunyan
Abstract : Purpose: Using the sample between 2005 and 2011, the purpose of this paper is to investigate the effect of a new fund entry on incumbents using the overlap measure in portfolio holdings. Design/methodology/approach: Empirical methodology is used in this study. Findings: The authors find that incumbents that have a higher overlap with the entrants underperform subsequently. Based on the characteristic-based approach ofDaniel et al. (1997), the authors find that the characteristic selectivity component is negatively correlated with the overlap measure, and thereby the decline in performance is driven by the stock-picking ability. The authors also discuss the unobserved actions of incumbents using the approach proposed byKacperczyk et al. (2008) and find that incumbent unobserved actions do not benefit mutual fund investors in China. Finally the authors find that investors respond to the supply-side competition between entrants and incumbents quickly. These findings help us understand the mutual fund completion in China. Originality/value: The findings in this study can help scholars, industry experts and regulatory authorities to understand the effect of competition in Chinese mutual fund industry.